Inovasi Pembelajaran Di Masa Pandemi: Peran LMS Moodle Dalam Mengembangkan Kemampuan Argumentasi Mahasiswa Pendidikan IPA - Gunawan Gunawan; Agus Abhi Purwoko; Agus Ramdani (Indonesian Publication Center, 2022)
The COVID-19 pandemic has spurred innovations in learning, particularly in the higher education sector, to ensure the continuity of teaching and learning processes. A significant innovation is the utilization of the Moodle-based Learning Management System (LMS). This study aims to investigate the role of Moodle LMS in developing the argumentation skills of Master of Science Education students at Mataram University during the pandemic. Employing a research and development (R&D) approach with the ADDIE model (Analysis, Design, Develop, Implementation, Evaluation) and a one-group pretest-posttest experimental design, the research involved Master of Science Education students enrolled in a Research Methods course. The results indicate a significant improvement in students' argumentation skills after being taught using Moodle LMS, with N-gain values in the high category. Specifically, the